HYGIENIC ASPECTS OF HEALTH STATUS OF THE WORKERS IN CHEMICAL AND PHARMACEUTICAL PRODUCTION - Горохова, Лариса Геннадьевна; Мартынова, Нина Андреевна; Кизиченко, Наталья Викторовна; Логунова, Татьяна Дмитриевна (Medicine in Kuzbass, 2017)
The specificity of chemical and pharmaceutical production is the use of a large number of chemical substances dangerous for health and life. Medical examinations at the enterprises of pharmaceutical industry showed the adverse picture with a predominance of respiratory diseases, suggesting the need for a thorough study of the toxic action of the substances used or produced in the synthesis process of medications. Medico-hygienic regulation is aimed at ensuring the disease prevention, nevertheless only a limited number of enterprises comply fully with hygienic regulations. One of the tools for making state management decisions aimed at preserving the health and improving the quality of life of the population is to calculate possible risks based on the principles of hygienic regulation aimed at the elimination or reduction of negative production impact.
Keywords: pharmaceutical production; occupational diseases; toxic action; risk assessment